2012
DOI: 10.1007/s10585-012-9470-8
|View full text |Cite
|
Sign up to set email alerts
|

RAF-kinase inhibitor protein (RKIP) downregulation in esophageal cancer and its metastases

Abstract: Raf kinase inhibitor protein (RKIP) is an inhibitor of Raf-mediated activation of mitogen-activated protein (MAP) kinase (MEK)-MAP kinase and is considered as an important tumor suppressor. RKIP-expression was investigated retrospectively in 321 esophageal cancers [179 adenocarcinomas (ACs), 142 squamous cell carcinomas (SCCs)]. RKIP-expression was further investigated in 41 precursor lesions consisting of 14 cases of non-dysplastic Barrett's mucosa, 5 low grade dysplasias (LGD), and 12 high grade dysplasias (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…This implies that progressive RKIP loss may play a key role in the pancreatic neoplastic transformation and that it is taking place even before invasion occurs. Similar findings were observed in a previous study concerning esophageal Barrett mucosa, where a down-regulation of RKIP was found in high-grade dysplasia compared with non-dysplastic lesions [32]. Our findings are partially in keeping with previous studies on RKIP expression on pancreatic cancer, which have also demonstrated a significant RKIP loss in cancer tissues compared with normal pancreatic tissue and an association of RKIP loss with presence of nodal and/or distant metastases as well as reduced patient survival [33,34].…”
Section: Discussionsupporting
confidence: 91%
“…This implies that progressive RKIP loss may play a key role in the pancreatic neoplastic transformation and that it is taking place even before invasion occurs. Similar findings were observed in a previous study concerning esophageal Barrett mucosa, where a down-regulation of RKIP was found in high-grade dysplasia compared with non-dysplastic lesions [32]. Our findings are partially in keeping with previous studies on RKIP expression on pancreatic cancer, which have also demonstrated a significant RKIP loss in cancer tissues compared with normal pancreatic tissue and an association of RKIP loss with presence of nodal and/or distant metastases as well as reduced patient survival [33,34].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that RKIP exhibits low expression levels in various cancers and it is often absent in metastasis [8,9,17,19,43,45,48,49,50,51,52,53,54,55,56,57,58,59,60]. RKIP loss has been suggested to result by hypermethylation of its promoter [41].…”
Section: Rkip Expression Patterns Across Different Cancer Typesmentioning
confidence: 99%
“…In addition, Gao et al reported that positive expression of RKIP in ESCC occurred significantly less often than in paratumor normal tissues, and that reduced RKIP expression was significantly correlated with a higher risk of recurrence, implying its importance in prognosis prediction (16). Furthermore, the expression level of RKIP was decreased in the order of dysplastic Barrett's mucosa, low-grade dysplasia, high-grade dysplasia and EAC, suggesting its involvement in esophageal carcinogenesis (17).…”
Section: Introductionmentioning
confidence: 99%